Pengaruh Karakteristik Personal terhadap Kinerja melalui Perilaku Kewirausahaan Petani Lada Muntok: The Influence of Personal Characteristics on Performance through Entrepreneurial Behavior of Muntok Pepper Farmers - Rufti Puji Astuti; Novyandra Ilham Bahtera; Eddy Jajang Jaya Atmaja; Igu Sandira (Society, 2020)
Currently, the performance of the pepper Muntok business continues to decline from time to time. This condition needs to be supported by studying the characteristics of farmers as human resources who carry out business planning and decision-making faced with various threats, challenges, and uncertainties. This study aims to 1) determine personal characteristics; 2) analyze the effect of personal characteristics on entrepreneurial behavior, 3) analyze the effect of personal characteristics and entrepreneurial behavior of farmers on business performance; and 4) analyze the effect of entrepreneurial behavior on business performance. The research method uses a survey method involving 90 farmers. Data analysis was carried out using Structural Equation Modeling (SEM) through Smart Partial Least squares (PLS). The results showed that the personal characteristics of the dominant farmer were strongly reflected by indicators of ethnic origin, experience, and age. Personal characteristics positively and significantly contribute to entrepreneurial behavior, and positive entrepreneurial behavior significantly influences business performance. The study results did not directly influence personal characteristics on business performance but through entrepreneurial behavior. Furthermore, the indicator variables of ethnic origin, experience, and age affect discipline, persistence, perseverance, interest in seeking and increasing knowledge, and mastery of technical skills, which can ultimately determine the level of business productivity and the desire to grow through business expansion. Before and during the COVID-19 pandemic, the entrepreneurial behavior of farmers was still strongly shaped by cognitive and affective variables. It is necessary to increase the skills of farmers through training and entrepreneurship development that pays attention to personal characteristics to improve business performance. This study can recommend the Agriculture Office of the Bangka Belitung Islands Province in formulating policies to increase the productivity of pepper plants and the welfare of pepper farmers in the future.